Tau exacerbates excitotoxic brain damage in an animal model of stroke - Mian Bi (Nature Portfolio, 2017)
Excitotoxicity contributes to neuronal injury following stroke. Here the authors show that tau promotes excitotoxicity by a post-synaptic mechanism, involving site-specific control of ERK activation, in a mouse model of stroke.